"A life-saving issue": the great commission as institutional policy in evangelical faith-based organizations in southern Ontario, Canada. Issue 4 (1st October 2020) - Gokani, Ravi; Caragata, Lea
ABSTRACT: This article presents data from a mixed-method study on evangelical faith-based organizations in Southern Ontario, Canada. The authors sought to explore the nature and extent of faith-sharing in these organizations by using the Convergent Triangulation Design, which permitted the use of semi-structured interviews, focus groups, surveys, and document review. First, The Great Commission acts as a de facto institutional policy in the evangelical faith-based organizations sampled; The Great Commission is a Biblical injunction, strongly observed by evangelicals, which states that evangelicals are commissioned by Jesus to share and ultimately convert others to their faith. The second theme is that in seeking to realize The Great Commission these organizations tried not to be coercive in sharing their faith. In the discussion, the paper explores briefly some of the potential ethical issues that emerge from faith-sharing in social service settings.